Implementación de un control basado en reglas a nivel coordinación para un caminado simétrico con una prótesis transfemoral activa - Meléndez-Calderón., A.; Caltenco-Arciniega., H. A.; Popovic., D. B.; Chong-Quero., J. E. (Revista Mexicana de Ingenieria Biomedica, 2008)
A Rule-Based Control (RBC) for “normal” walking off a Transfemoral Prosthesis (TFP) was developed for its implementation in a microcontroller. The advantages of using this type of control over analytical methods are described, as well as the results obtained in the Gait Cycle Analysis, the rule generation, the programming structure and the most relevant conclusions obtained in work realized in [1,2] at the Control Department of Aalborg University (Denmark) in collaboration with the Center for Sensory Motor Interaction (SMI) of such University.